The Role of PPAR Ligands in Controlling Growth-Related Gene Expression and their Interaction with Lipoperoxidation Products. (6th July 2008) - Barrera, Giuseppina; Toaldo, Cristina; Pizzimenti, Stefania; Cerbone, Angelo; Pettazzoni, Piergiorgio; Dianzani, Mario Umberto; Ferretti, Carlo
Abstract : Peroxisome proliferators-activated receptors (PPARs) are ligand-activated transcription factors that belong to the nuclear hormone receptor superfamily. The three PPAR isoforms (α, γ andβ / δ ) have been found to play a pleiotropic role in cell fat metabolism. Furthermore, in recent years, evidence has been found regarding the antiproliferative, proapoptotic, and differentiation-promoting activities displayed by PPAR ligands, particularly by PPARγ ligands. PPAR ligands affect the expression of different growth-related genes through both PPAR-dependent and PPAR-independent mechanisms. Moreover, an interaction between PPAR ligands and other molecules which strengthen the effects of PPAR ligands has been described. Here we review the action of PPAR on the control of gene expression with particular regard to the effect of PPAR ligands on the expression of genes involved in the regulation of cell-cycle, differentiation, and apoptosis. Moreover, the interaction between PPAR ligands and 4-hydroxynonenal (HNE), the major product of the lipid peroxidation, has been reviewed.